Intestinal parasitic infection in commercial chickens in Sirajgonj - Islam, Md Shadiul; Dey, Anita Rani; Parvin, Shanaz; Farjana, Thahsin; Alam, Mohammad Zahangir (Journal of the Bangladesh Agricultural University, 2020)
Endoparasitism is among the important causes of reduced productivity of chickens. To investigate the prevalence of intestinal parasitic diseases, a study was carried out from March, 2017 to February, 2018 in dead broiler and sonali chickens from different commercial farms in Sirajgonj district by postmortem examination. A total of 500 intestinal samples (250 broilers and 250 sonali) were examined for the presence of worms and coccidian infection in the lumen of intestine. Among examined birds, 41 (16.4%) broiler and 56 (22.4%) sonali chickens were found to be infected with intestinal parasitic diseases including ascaridiasis (Ascaridia galli), raillietiniasis (Raillietina spp.) and coccidiosis (Eimeria spp.). Among these three, coccidiosis was the most predominant parasitic diseases (9.2% and 14.4%) followed by ascaridiasis (5.6% and 7.6%) and raillietiniasis (1.6% and 0.4%) in broiler and sonali chickens, respectively. The prevalence of intestinal parasitic diseases were significantly higher (p<0.01) in older broiler (>3 weeks- 31.8%) and sonali (5-9 weeks- 30.3%) birds than in young broiler (≤3 weeks- 4.3%) and sonali (1-4 weeks- 10.5%) birds. Female birds (23.1%) were 1.63 times more prone to intestinal parasitic diseases than male birds (15.5%) and it was statistically significant (p 0.05). In farm management system, significantly higher intestinal parasitic infection was recorded in deep litter system (23.5%) than in slatted system (11.6%). Significantly higher infection was observed during rainy season (26.5%), followed by summer (19.4%) and winter season (10.3%). It could be concluded that intestinal parasitic infections were prevalent in commercial poultry farms in the study area. Also, chickens irrespective of age, sex, management practices and seasons of the year were significantly associated with intestinal parasitic diseases that play an important role in decreased production in commercial poultry farms in Bangladesh. J Bangladesh Agril Univ 18(1): 111–116, 2020